Analisis Faktor Resiko Diare pada Balita di Wilayah Kerja Puskesmas Gading Kota Surabaya - Perwitasari, Yulinda Ayu; Ningrum, Astika Gita; Puspitasari, Dwiyanti; Fatmaningrum, Widati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Various factors can affect the likelihood of toddlers developing diarrhea. Numerous studies have emphasized the role of hygiene factors, including food and beverage hygiene, maternal knowledge, exclusive breastfeeding, and handwashing practices, on toddler diarrhea prevalence. Given that diarrhea can lead to significant adverse events (KLB), identifying root causes is essential to reduce its occurrence in toddlers. This research aimed to determine the risk factors linked to diarrhea in toddlers within the Gading Health Center's operational area in Surabaya City. The study utilized a quantitative analytical observational method with a cross-sectional design. The population included mothers of toddlers aged 0-59 months who had been examined and lived in the Gading Health Center's area, with 125 samples selected through consecutive sampling. A questionnaire focused on variables such as exclusive breastfeeding, knowledge of diarrhea, food and beverage sanitation hygiene, and handwashing practices was used for data collection. The collected data were analyzed using the chi-square test. In the Gading Health Center's operational area in Surabaya City, 52% of toddlers had experienced diarrhea. While no significant correlation was found between toddler diarrhea and mothers' handwashing practices (p=0.065), significant associations were noted between toddler diarrhea and exclusive breastfeeding (p=0.005), maternal knowledge (p<0.001), and food and beverage sanitation hygiene (p=0.007).